Clinical presentation of older children with congenital adrenal hyperplasia: an important outcome for newborn screening policy. (29th September 2015) - Knowles, R; Khalid, JM; Oerton, J; Hindmarsh, P; Kelnar, C; Dezateux, C
Abstract : Background: Congenital adrenal hyperplasia (CAH) is caused by recessively inherited enzyme deficiencies in cortisol production and affects an estimated one child in every 10 000–20 000 born. Clinical presentations after the neonatal period include precocious puberty, accelerated growth or fertility problems. These may have long-term irreversible consequences, yet information about their frequency is lacking. Aim: To report the spectrum of CAH in UK children presenting after the first year of life, and its distribution by sex, ethnicity and clinical features at presentation, with the aim of informing newborn screening policy. Methods: Active surveillance through the British Paediatric Surveillance Unit for 25 months from August 2007 of newly diagnosed CAH in any child 0–15 years with clinical features of CAH and elevated 17-hydroxyprogesterone. Cases were assigned as "definite CAH", "probable CAH" or "not CAH" following review by an expert panel. Clinician reports of ethnicity, based on UK census categories, were grouped as White, Black, Asian and Mixed/Other. Results: 131 children were notified in the first 24 months of surveillance, of whom 51 (40%) were diagnosed between 1–15 years of age with CAH of the following subtypes: 21-hydroxylase deficiency (n=36), 11 β-hydroxylase deficiency (n=6), 9 children not yet determined. 14/51 (28%) were Asian compared with 4% of the UK child population and 29/51 (57%; 95% CI 43 to 69%) were girls. Median age at presentation was 6 years (IQR 5–9). In the majority, first presentation was with precocious puberty (36/51; 71%). Two children presented with adrenal insufficiency but a further six went on to have episodes of adrenal insufficiency. 37/51 (73%) had advanced bone age and/or accelerated growth at presentation. One girl, presenting with virilisation, had undergone genital surgery at the time of notification. Conclusions: In the UK each year approximately 25 children present for the first time with CAH after the 1 year of age. The majority have features of precocious puberty and/or advanced bone age at diagnosis which are largely irreversible and have long-term implications. Our study highlights the potential of newborn screening to avoid or mitigate advanced and irreversible clinical manifestations in children presenting with CAH after 1 year of age.